A Model of Dual Labor Markets When Product Demand Is Uncertain - Rebitzer, J. B.; Taylor, L. J. (Quarterly Journal of Economics, 1991)
James B. Rebitzer, Lowell J. Taylor; A Model of Dual Labor Markets When Product Demand Is Uncertain*, The Quarterly Journal of Economics, Volume 106, Issue 4, 1